Chapter Musea voor een betere wereld - Prak, Maarten (Amsterdam University Press, 2023)
Over the last forty years, 'the world' has entered 'the museum'. Collections and presentations that were supposed to be self-evident had to be reconsidered. This chapter demonstrates that two more or less simultaneous influences shaped this process in Dutch museums. On the one hand, many Dutch museums were transformed from institutions of the local or national government into independent charities and forced to take greater responsibility for their own finances. On the other hand, the social exclusivity of the collections and presentations (dominated by white males) was questioned. The article describes how museums dealt with these challenges and their sometimes contradictory implications.